Excluding evidence (or staying proceedings) to vindicate rights in Irish and English law1. (14th April 2015) - Ward, Tony; Leon, Clare
Abstract : The constitutional duty of the Irish state 'to defend and vindicate the personal rights of the citizen' is the basis of a strict rule excluding unconstitutionally obtained evidence. Although English courts recognise a similar duty to 'vindicate human rights and the rule of law', their powers to exclude evidence or stay proceedings for abuse of process are extremely flexible and discretionary. In both jurisdictions, there has been particular controversy over the application of these powers to covert recordings that breach legal professional privilege. This paper argues that the duty to vindicate rights and the rule of law underpins both the exclusion of unlawfully obtained evidence and the punishment of offenders. It requires a balancing exercise, not between defendants' rights and an incommensurable public interest but, rather, between two aspects of the same constitutional duty of the courts.